The relationship of physical activity to high-density lipoprotein cholesterol level in a sample of community-dwelling older adults from Amazonas, Brazil. (November 2017) - Gouveia, Élvio R.; Ihle, Andreas; Kliegel, Matthias; Freitas, Duarte L.; Jurema, Jefferson; Tinôco, Maria A.; Odim, Angeany; Machado, Floramara T.; Muniz, Bárbara R.; Antunes, António A.; Ornelas, Rui T.; Gouveia, Bruna R.
Highlights: HDL-C seems to be protective in the development of CVD. This is particularly important in older adults, due to their vulnerability. HDL-C was positively related to physical activity and socioeconomic status, but negatively related to smoking and body fat distribution. This study suggests that PA should be considered a major factor in recommendations to prevent low HDL-C, independently of age and sex. Abstract: Objectives: (1) To study the relation of physical activity (PA) to high-density lipoprotein cholesterol (HDL-C) and (2) to investigate if the strength of these associations holds after adjustments for sex, age, and other key correlates. Methods: This study included 550 older adults from Amazonas. HDL-C was derived from fasting blood samples. PA at sport and leisure, smoking, alcohol consumption, and socioeconomic status (SES) were interviewed. Waist circumference (WACI) was assessed. Results: HDL-C was positively related to PA sport, PA leisure, and SES (0.22 ≤ r ≤ 0.34; p ≤ 0.001) and negatively related to smoking and WACI (r ≤ −0.10; p < 0.05). Controlling for sex and age did not affect these relationships. Hierarchical multiple regression analyses showed that the relation of HDL-C to PA sport and leisure remained significant when controlling for all other investigated correlates (0.14 ≤ β ≤ 0.24; p ≤ 0.001). Discussion: In order to prevent low HDL-C in older adults, promoting PA seems to be an important additional component besides common recommendations concerning weight reduction.